Spinal TRPC6 channels contributes to morphine-induced antinociceptive tolerance and hyperalgesia in rats. (3rd February 2017) - Jin, Hua; Sun, Ying-tong; Guo, Guang-qiong; Chen, Da-lin; Li, Yu-jin; Xiao, Gao-peng; Li, Xin-nan
Highlights: TRPC6 inhibition attenuated morphine withdrawal-induced hyperalgesia. TRPC6 inhibition suppressed morphine tolerance. TRPC6 inhibition suppressed morphine-induced increased levels of CaMKIIα and nNOS. TRPC6 inhibition blocked morphine-induced neuroinflammation. Abstract: The chronic administration of opioids results in the development of morphine analgesic tolerance and withdrawl-induced hyperalgesia, which limits their clinical utility in pain treatment. However, the cellular mechanisms underlying opioid-induced tolerance and hyperalgesia are not fully understood. The transient receptor potential canonical channel TRPC6 is important for brain development and function, as it regulates cytosolic, endoplasmic reticulum, and mitochondrial Ca 2+ levels in neural cells. Here, we report that TRPC6 expression in the spinal cord was up-regulated after chronic morphine treatment. Furthermore, inhibition of TRPC6 in the spinal cord blocked the induction of morphine tolerance and hyperalgesia without affecting basal pain perception. These effects were attributed to the attenuation of morphine-induced neuroimmune activation and increased levels of CaMKIIα and nNOS in the spinal cord. This data suggests that specific TRPC6 inhibitors could be utilized for the prevention of morphine-induced antinociceptive tolerance and hyperalgesia in chronic pain management.